Non-precious metal electrocatalysts for hydrogen production in proton exchange membrane water electrolyzer - Kim, Hoyoung; Hwang, Eunkyoung; Park, Hyanjoo; Lee, Byung-Seok; Jang, Jong Hyun; Kim, Hyoung-Juhn; Ahn, Sang Hyun; Kim, Soo-Kil (ELSEVIER, 2017)
Electrodeposited CuxMO100-x catalysts were prepared on a Ti substrate for the hydrogen evolution reaction (HER) in acidic medium. By varying the electrolyte composition for electrodeposition, the atomic concentration of the CuxMO100-x electrocatalysts could be controlled, and the Mo content ranged between 0.8 and 6.9%. In the first cyclic voltammetry scan in a 0.5 M H2SO4 electrolyte, the recorded HER current densities of the CuxMo100-x, electrocatalysts at-0.50 V-RHE increased on increasing the Mo content to 3.8%; then, a further increase in Mo to 6.9% led to a saturation in the HER activity. The maximum value of the normalized current density with respect to the electrochemical surface area and the loading mass was found for the Cu99.2MOo.8 electrocatalyst. Characterization of the prepared catalysts revealed that the enhancement of catalytic activity originates from changes in the grain size and electronic structure. To operate a single cell of the proton exchange membrane water electrolyzer (PEMWE), we electrode posited CuMo catalyst on carbon paper, and this was used as the cathode, while IrO2 electrodeposited on carbon paper was used as the anode. The cell performance was normalized with respect to the metal mass loading and was found to be 3.4 A/mg(metal) at 1.9 V, a 2.2-10.8 times better catalyst cost-activity relationship compared to that of currently reported PEMWEs using Pt-based cathodes. Consequently, the results presented here show that non-noble metal cathodes can be used for PEMWE operation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: OXYGEN EVOLUTION REACTION; EFFICIENT ELECTROCATALYST; ALLOY CATALYSTS; WS2 NANOSHEETS; MOLYBDENUM; NI; OXIDATION; IRIDIUM; NICKEL; COPPER